Avaliação dos aspectos da qualidade da água na sub-bacia hidrográfica do arroio Cadena - município de Santa Maria - RS - Ceretta, Maristela Coradini (2004)
The dynamic of occupation and land uses in the drainage area of the Cadena creek is the most important aspect that has led to the degradation of water quality. Cadena stream is part of the large Vacacaí basin, located in central Rio Grande do Sul sate, Brazil. This work consists of the stablishment of a monitoring program to determine water quality indices and to estimate the pollutant loads resulting of anthropic sources. Appropiate Thus, there was stablished the modulation of the basin through the implantation of a monitor net formed by three hydrometric points the measurement of the eviction and collection of water to determine the variations of quality. The results of this monitoration realized in the period from november 2002 to november 2003, shows that the quality of the water in the sub-basin varies between Regular and too bad according to the interpretation of the indice of Quality of the Water IQA NSF* (product) and the IQA NSF (sum). The amount of specific organic load in the basin is estimated around 18,69 Kg. DBO/day/km2 mainly due the throwing of sewage in the drainage system. The modulation of the hydrografical basin allowed us to attribute the organic loads to the respective different sector of occupation (urban, rural and urban-rural) in the refered hydrografical basin.